Meningkatkan Kesadaran Partisipasi Generasi Z dan Pemahaman Pemilu yang Berasaskan Luber Jurdil di Kelurahan Sanur: Increasing Awareness of Generation Z Participation and Understanding of Elections Based on Luber Jurdil in Sanur District - Mulyadi, Made; Putra, I Putu Nadha Ambara (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Elections in Indonesia are an integral part of the democratic system, ensuring people's participation and asserting their sovereignty. The 2024 election is of particular concern due to a significant increase in the participation of first-time voters, especially Generation Z. Although their participation rates are increasing, there is also a group of non-voters who abstain from exercising their right to vote. The importance of understanding the principles of Luber Jurdil in elections, as mandated by the 1945 Constitution of the Republic of Indonesia, needs to be emphasized to create democratic elections. The main problem formulation includes efforts to increase the participation of Generation Z and understanding the principles of Luber Jurdil in Banjar Sindu Kaja. The purpose of this activity is to understand efforts that can be made to increase the participation of Generation Z in elections and their understanding of Luber Jurdil in Banjar Sindu Kaja, Sanur Subdistrict. Socialization activities at the Sekaa Teruna Teruni Sindu Putra in Banjar Sindu Kaja, Sanur Subdistrict aim to increase the participation of Generation Z in the 2024 elections and strengthen their understanding of the principles of Luber Jurdil. It is hoped that through this socialization, Generation Z can become more aware of their role in the political process and be able to vote wisely and responsibly.